Serial multiple mediation of psychological empowerment and job burnout in the relationship between workplace bullying and turnover intention among Chinese novice nurses - Liping Ren; Hyunli Kim (Wiley, 2023)
Abstract Aim This study aimed to examine the direct and indirect effects of workplace bullying on turnover intention using the serial multiple mediators of psychological empowerment and job burnout. Design A cross‐sectional study was conducted. Methods A convenience sample of 506 novice nurses from five Triple A hospitals in China's S province from November 2020 to February 2021 and were evaluated using online questionnaires on workplace bullying, psychological empowerment, job burnout, and turnover intention. Results The prevalence of turnover intention was 51.9%. In the serial multiple mediator model, workplace bullying had a direct effect (c = 0.452, p < 0.001) and indirect effect (c' = 0.229, p < 0.001) on turnover intention through the serial multiple mediators of psychological empowerment (B = −0.093, p = 0.020) and job burnout (B = 0.127, p < 0.001); hence, the proposed model explained the total variance of 32.2% in turnover intention. Patient or public contribution Nursing managers should use effective measures for strengthening the psychological empowerment to minimize novice nurse burnout and turnover intention resulting from workplace bullying.